Clinical features of non-syndromic late developing supernumerary teeth: a sign of the third dentition? - Xiaoqing Li; Xu Gong; Min Yu; Xuemei Gao (BMC, 2024)
Abstract Objectives This study aimed to summarize the clinical features of non-syndromic late developing supernumerary teeth (LDST) and comparisons with common supernumerary teeth (ST) and explore the association between LDST and the third dentition. Materials and methods This study retrospected cone-beam computed tomography (CBCT) and medical history of 41,903 consecutive patients from January to December 2021. Comparisons between ST and LDST were evaluated by Chi-square test or Fisher exact test. Correlation between chronological age and dental stage age was evaluated by Spearman's rank correlation coefficient. Binary logistic regression analysis was used to explore the features of LDST originating from the third dentition. Results Sixty patients with 126 non-syndromic LDST and 1602 patients with 1988 non-syndromic ST were identified. The prevalence of ST and LDST was 3.82% and 0.14%, respectively, with a male-female ratio of 1.78:1 and 1.31:1. LDST patients mainly had LDST in multiple (58.33%) and bilaterally (41.67%), with an average of 2.1/patient. Most LDST were normal-shaped (84.13%), vertically oriented (71.43%), located in the mandible (80.16%), and distributed in the premolar region (82.54%). The study also indicated that the development of LDST was correlated with permanent teeth, with LDST developing 6.48 to 10.45 years later. In this study, 72.22% of LDST met the clinical criteria for the third dentition. Conclusions LDST manifested different clinical features from common ST. LDST might be closely related to the third dentition. Clinical relevance This work would help to comprehend LDST from a clinical perspective, and may be complementary to the criteria of the third dentition.